Primary care patients' perspectives on the use of non-pharmacological home remedies in Geneva: a cross-sectional study - Neria E. Winkler; Paul Sebo; Dagmar M. Haller; Hubert Maisonneuve (BMC, 2022)
Abstract Background Home remedies are anchored in patients' everyday life, but their use in Western cultures remains scarcely explored. Our objectives were to investigate primary care patients' perspectives and use of non-pharmacological home remedies in Geneva (Switzerland). Methods In spring 2020, we conducted a cross-sectional survey among adult primary care patients in randomly selected general practices (N = 15). Patients were recruited in the waiting rooms and asked to complete a questionnaire about their sociodemographic characteristics, their home remedy use, and their expectations and reasons for using (or not using) home remedies. We employed descriptive statistics to summarise the data and logistic regression adjusted for clustering within practices to explore associations between home remedy use and participants' sociodemographic characteristics. Results Three hundred fourteen of three hundred ninety patients agreed to participate in the study (participation rate 80.5%). Home remedies were used by 64.4% of patients. The main reasons given were for preventive purposes (55.3%), self-care (41.0%), as an alternative to conventional medicine (40.5%) and to avoid or delay a medical consultation (38.5%). One-third of patients considered that it was the GP's role to spontaneously inform them about home remedies (36.4%), another third considered that it was the GP's role to inform them, but only upon specific request (32.3%), and the last third of patients declared that it was not the GP's role to provide information about home remedies (30.3%). Patients living in an urban zone (adjusted OR 2.1; 95%CI 1.0-4.4; p 0.05) and those with a tertiary education background (adjusted OR 1.9; 95%CI 1.0-3.6; p 0.05) believed that it was their GP's role to inform them about home remedies. Conclusions Home remedies are used by a majority of primary care patients in Geneva. For a comprehensive and safe healthcare management in the context of patient-oriented medicine, more evidence-based research on efficacy and safety of home remedies as well as their place in primary care consultation is required.